1997
DOI: 10.1021/bi971599r
|View full text |Cite
|
Sign up to set email alerts
|

A New Type of DNA Minor-Groove Complex:  Carbazole Dication−DNA Interactions

Abstract: The effect of opportunistic infections (OI) on immune-compromised populations has been known for decades, but the recent AIDS epidemic has sparked renewed interest in the development of new anti-OI agents. The mechanism of action of a series of cationic unfused-aromatic anti-OI drugs is believed to involve binding of the drug to AT sequences in the minor groove of DNA. Some new anti-OI drug candidates have been synthesized with fused aromatic ring systems (e.g. carbazoles) that do not resemble the classical pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
64
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 33 publications
9
64
0
Order By: Relevance
“…A number of additional classes of biscationic DNA binding compounds have been synthesized and found to demonstrate cytotoxicity against P. carinii in rat models of PCP. These include substituted bisbenzimidazoles linked 2,2Ј through alkyl groups (65), various derivatives of pentamidine (25,64), diarylfurans (8), and carbazoles (60). It has been suggested, on the basis of their cytotoxicity for P. carinii and their minor-groove binding properties (4,20), that some or all of these compounds act by poisoning or inhibiting topoisomerase I or II.…”
Section: Discussionmentioning
confidence: 99%
“…A number of additional classes of biscationic DNA binding compounds have been synthesized and found to demonstrate cytotoxicity against P. carinii in rat models of PCP. These include substituted bisbenzimidazoles linked 2,2Ј through alkyl groups (65), various derivatives of pentamidine (25,64), diarylfurans (8), and carbazoles (60). It has been suggested, on the basis of their cytotoxicity for P. carinii and their minor-groove binding properties (4,20), that some or all of these compounds act by poisoning or inhibiting topoisomerase I or II.…”
Section: Discussionmentioning
confidence: 99%
“…Structures with rigid frameworks of fused ring systems as linkers for the dicationic groups (e.g. carbazole, benzofuran, benzothiophene, 9H-fluorene, fluorenone, acridine and anthraquinone) were also reported as effective antimicrobial agents [22][23][24][25] and had high DNA minor groove binding affinity and postulated to involve water mediated interactions [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies from our laboratory have demonstrated that guanidine dications display considerable affinity to AT rich sites of the DNA minor groove and possess interesting antiprotozoan activity [25,[28][29][30]. In light of the previous results, we have designed and performed a study aiming at combining the novelty of a rigid rod-like terphenyl framework bearing a bisguanidine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In searching for a small molecule in which to install a chirality element, we were attracted to the numerous reports of DNA polymorphs binding with substituted carbazoles, resulting in a wide variety of biological activities including anti-protozoal (Tanious et al, 1997;Arafa et al, 2005), G-quadruplex stabilization (Huang et al, 2008), and anti-tumour and anti-infectious activities (Dias et al, 2004;Stover et al, 2009). We recognized that hydroxycarbazole 1 could be dimerized via an oxidative coupling to generate the axially chiral biaryl BICOL (Scheme 1).…”
mentioning
confidence: 99%